Effects of CRISPR/Cas9 dosage on TICAM1 and RBL gene mutation rate, embryonic development, hatchability and fry survival in channel catfish. Issue 1 (December 2018) - Elaswad, Ahmed; Khalil, Karim; Ye, Zhi; Liu, Zhanjiang; Liu, Shikai; Peatman, Eric; Odin, Ramjie; Vo, Khoi; Drescher, David; Gosh, Kamal; Qin, Guyu; Bugg, William; et al.
Abstract The current study was conducted to assess the effects of microinjection of different dosages of guide RNA (gRNA)/Cas9 protein on the mutation rate, embryo survival, embryonic development, hatchability and early fry survival in channel catfish, Ictalurus punctatus . Guide RNAs targeting two of the channel catfish immune-related genes, toll/interleukin 1 receptor domain-containing adapter molecule (TICAM 1) and rhamnose binding lectin (RBL) genes, were designed and prepared. Three dosages of gRNA/Cas9 protein (low, 2.5 ng gRNA/7.5 ng Cas9, medium, 5 ng gRNA/15 ng Cas9 and high, 7.5 ng gRNA/22.5 ng Cas9) were microinjected into the yolk of one-cell embryos. Mutation rate increased with higher dosages (p  < 0.05). Higher dosages increased the mutation frequency in individual embryos where biallelic mutations were detected. For both genes, microinjection procedures increased the embryo mortality (p  < 0.05). Increasing the dosage of gRNA/Cas9 protein increased the embryo mortality and reduced the hatching percent (p  < 0.05). Embryonic development was delayed when gRNAs targeting RBL gene were injected. Means of fry survival time were similar for different dosages (p  > 0.05). The current results lay the foundations for designing gene editing experiments in channel catfish and can be used as a guide for other fish species.